Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00024-016-1277-0
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami Characteristics Along the Peru–Chile Trench: Analysis of the 2015 Mw8.3 Illapel, the 2014 Mw8.2 Iquique and the 2010 Mw8.8 Maule Tsunamis in the Near-field

Abstract: Tsunamis occur quite frequently following large magnitude earthquakes along the Chilean coast. Most of these earthquakes occur along the Peru-Chile Trench, one of the most seismically active subduction zones of the world. This study aims to understand better the characteristics of the tsunamis triggered along the Peru-Chile Trench. We investigate the tsunamis induced by the Mw8.3 Illapel, the Mw8.2 Iquique and the Mw8.8 Maule Chilean earthquakes that happened on September 16th, 2015, April 1st, 2014 and Februa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Because the trench to coast distance along the Chilean margin is smaller than in typical subduction zones, a significant portion of the seismogenic zone extends beneath land, leading to a trade-off between uplift of land versus that beneath the sea (Figure 1). Omira et al [2016] showed, for example, that the 2010 earthquake proportionally expended more initial tsunami energy for inland deformation than did the later events in 2014 and 2015. This sensitivity of the overall tsunami size to source depth in the Chilean megathrust is further supported by tsunami modeling, which shows that earthquakes that concentrate slip at deeper than typical depths produce smaller tsunamis and greater coastal uplift than those resulted from earthquakes with typical or shallower concentrations of slip [Carvajal and Gubler, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Because the trench to coast distance along the Chilean margin is smaller than in typical subduction zones, a significant portion of the seismogenic zone extends beneath land, leading to a trade-off between uplift of land versus that beneath the sea (Figure 1). Omira et al [2016] showed, for example, that the 2010 earthquake proportionally expended more initial tsunami energy for inland deformation than did the later events in 2014 and 2015. This sensitivity of the overall tsunami size to source depth in the Chilean megathrust is further supported by tsunami modeling, which shows that earthquakes that concentrate slip at deeper than typical depths produce smaller tsunamis and greater coastal uplift than those resulted from earthquakes with typical or shallower concentrations of slip [Carvajal and Gubler, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…It is the efficient trapping of tsunami energy that leads to the long duration, and not, as in the Tohoku-oki case, simply the sheer size of the event. As another example, consider the 2014 M8.1 Iquique, Chile, earthquake, that event generated a tsunami with an estimated initial potential energy of 1.5 × 10 13 J (Omira et al, 2016), a quantity similar in magnitude to that of the Tehuantepec event.…”
Section: Implications For Hazardsmentioning
confidence: 96%
“…The co-seismic deformation occurs partially onshore, resulting in shoreline subsidence or uplift for the 2010 Maule, 2014 Iquique, and 2015 Illapel, Chile events (Omira et al 2016). Fritz et al (2011) measured a maximum runup height of 29 m decaying fast from this maximum value to values between 5 and 10 m for the Maule event.…”
Section: Tablementioning
confidence: 99%